Cesarean Scar Pregnancy Treated by Systemic or Local Methotrexate Administration Followed by Hysteroscopic Removal: A Comparative Pilot Study - Giancarlo Garuti; Paola Francesca Sagrada; Lorenzo Sogaro; Serena Migliaccio; Marilena Farella; Marco Soligo (IMR Press, 2023)
Background: Cesarean Scar Pregnancy (CSP) is a life-threatening condition following an ectopic implantation within the scar of a previous cesarean delivery and no guideline is shared about optimal treatment options. Methods: We present a retrospective study comparing the outcomes of patients with CSP diagnosed before the 10th week of gestation treated by systemic or local Methotrexate (MTX) for pregnancy termination, followed by hysteroscopic placental removal. After MTX administration, the weekly decrease-rate of beta Human Chorionic Gonadotropin subunit (β-HCG) was adopted as criterion to indicate a repeated MTX dose (less than 25% decline after 2 weeks) and to surgery timing (50% decline in two consecutive assessments). Results: Fourteen patients satisfied the inclusion criteria. Eight and six of them underwent systemic (group A) and local (group B) MTX administration, respectively. No significant difference was found in pre-treatment and intra-operative variables. Group B showed significantly accelerated times in weekly halving of β-HCG with respect to group A (p-value = 0.005). Accordingly, the elapsing time between MTX and surgery was found to be significantly longer in the group A than in the group B (p-value = 0.016). In group B no patient required further MTX administration whereas 3 out of 8 patients from group A required an additional MTX dose. In all patients hysteroscopic surgery resulted uneventful and no further treatment was required. Conclusions: When followed by hysteroscopic placental removal, systemic or local MTX administration resulted effective to treat CSP. Local MTX allows quicker trophoblastic demise, leading to significant anticipation of surgery with respect to systemic administration.